Sexism, rape myths and feminist identification explain gender differences in attitudes toward the #metoo social media campaign in two countries. Issue 5 (3rd September 2019) - Kunst, Jonas R.; Bailey, April; Prendergast, Claire; Gundersen, Aleksander
ABSTRACT: On October 15, 2017, actress Alyssa Milano popularized the #metoo campaign, which sought to expose the prevalence of sexual harassment and assault in public domains by encouraging victims to share their experiences on social media using the hashtag metoo . The online campaign rapidly grew to a global phenomenon, which was generally well supported. However, some criticized the campaign online as a battle of the sexes, which pits men against women. Our cross-cultural research investigated whether gender differences in attitudes and feelings toward #metoo are due to underlying differences in ideologies and experiences that only partly overlap with gender. We surveyed respondents in the United States, where the campaign began, and in Norway, a highly gender-egalitarian country. In both countries, men expressed less positivity toward #metoo than women and perceived it as substantially more harmful and less beneficial. These gender differences were largely accounted for by men being higher than women in hostile sexism, higher in rape myth acceptance, and lower in feminist identification. The results, hence, suggest that gender differences in attitudes to social media campaigns such as #metoo might be best characterized as dimensional ideological differences rather than fundamental group differences.